Health, wellness, and fitness training: A pilot study on preparing physically fit and police academy-ready graduates - DeNysschen, Carol A. (International journal of police science & management, 2018)
Law enforcement can be a physically and mentally demanding occupation. It is well known that health and fitness is highly related to job performance, career longevity and safety. There is insufficient research on the development of higher education-based coursework in criminal justice programs that emphasize the development of healthful behavior patterns and physical fitness. The purpose of this study was to determine if successful completion of a 14-week health education and fitness training course would increase participants’ physical fitness and capabilities to perform essential physical fitness tasks needed for a career in law enforcement. Fifty-one college students participated in a health promotion program that included multiple components of wellness such as physical fitness, exercise principles, healthy eating behaviors, goal setting and stress management. Results indicated that a college-based health promotion course can successfully prepare physically fit and police academy-ready criminal justice graduates that have an educational foundation in healthy lifestyle.